PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS NASABAH DEPOSITO PT. BANK DANAMON INDONESIA TBK KCP MEDAN AHMAD YANI - Vincent, Vincent; Sutanto, David; Maharany, Maharany; Yunior, Khomeiny (EDUTECH CONSULTANT, 2019)
The purpose of this study is to examine the effect of service quality variables and promotion on customer loyalty. Decrease in customer loyalty can be seen from the number of customers who stopped due to the quality of service that has not been satisfactory and the promotion has declined. The method used in this study is a quantitative approach, this type of research is quantitative descriptive, and the nature of this research is descriptive explanatory. The method of data collection is done by interviews, questionnaires, and documentation. The data analysis method used is multiple regression. The population is 147 customers, a sample of 107 customers of PT. Bank Danamon Indonesia Tbk. Medan Ahmad Yani Branch. The results showed that simultaneously and partially service quality and promotion had a positive and significant effect on Customer Loyalty PT. Bank Danamon Indonesia Tbk. Medan Ahmad Yani Branch (Deposit Products). The magnitude of the coefficient of determination is 25.5% of the variable customer loyalty which can be explained by service quality and promotion variables while the rest is explained by other variables not examined in this study.